The Relationship of the Sural Nerve and Anatomic Landmarks Relevant to the Extensile Lateral and Sinus Tarsi Approaches: A 3T MRI Study. Issue 1 (January 2022) - Ghetti, Claudio B.; Mitchell, Brendon; Shah, Vrajesh J.; Huang, Brady K.; Kent, William; Foran, Ian M.
Category: Hindfoot; Trauma Introduction/Purpose: The extensile lateral and sinus tarsi approaches are commonly used during foot and ankle surgery, and pose a risk of iatrogenic injury to the sural nerve, a cutaneous nerve that innervates the ankle and lateral foot. Our understanding of the SN's location is based primarily on anatomic cadaver studies with small sample sizes. Our research analyzes a large cohort of high-field 3 Tesla (3T) magnetic resonance images (MRI) of the ankle to obtain a more generalizable, in-vivo sample of the distal course of the SN. A better understanding of the course and variability of the sural nerve will allow surgeons to minimize the risk of iatrogenic injury to the SN. Methods: High-field 3T MRI studies of the ankle performed at our institution between January 2015 and December 2020 were analyzed. The vertical distance of the SN to the distal tip of the lateral malleolus (DTLM), horizontal distance of the SN to the DTLM, and the lateral border of the Achilles tendon (LBA) at the level of the DTLM were measured by 3 blinded reviewers. Also measured was the horizontal distance of the SN to the LBA at the level of superior Achilles insertion (SAI) onto the calcaneus, as well as 5 cm above the SAI. We then analyzed upper and lower quartile ranges to compare the outer anatomic distribution frequencies of the SN to the locations of common approach incision lines. This outer limit analysis may serve to quantify the variability of the SN. Results: A total of 204 3T MRIs of the ankle were included. 1st and 4th quartile ranges for vertical distance from the SN to the DTLM were 0.9-1.9 cm and 2.5-3.6 cm respectively. 1st and 4th quartile ranges for horizontal distance of the SN to the DTLM at the level of DTLM were 0.8-1.5 cm and 2.0-3.0 cm respectively. 1st and 4th quartile ranges for horizontal distance of SN to the LBA at the level of DTLM were 1.0-1.6 cm and 2.1-2.9 cm respectively. 1st and 4th quartile ranges for horizontal distance of SN to the LBA at the level of the SAI were 1.4-2.3 cm and 2.8-3.7 cm respectively. 1st and 4th quartile ranges for horizontal distance of SN to the LBA, 5 cm above SAI were 0.4-0.8 cm and 1.0-1.8 cm, respectively. Conclusion: The vertical distance from SN to DTLM was greater than the previously reported maximum of 2.6cm in 25% of cases. This highlights the risk of injury to the sural nerve with the extensile lateral approach. Our first quartile range for vertical distance of SN to DTLM of 0.9-1.9cm indicates that even at the lowest range of values, the SN remains clear of the incision line used in the sinus tarsi approach, which extends from the DTLM to the base of the fourth metatarsal. The sural nerve is still at risk during posterior extension or retraction of the sinus tarsi incision.